2021
DOI: 10.1080/17439760.2021.1871938
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional age differences in 24 character strengths: Five meta-analyses from early adolescence to late adulthood

Abstract: The present study comprises five meta-analyses (47 samples with a total N of 1,098,748) that investigate cross-sectional age differences in the 24 character strengths entailed in the VIA model. It is expected that most strengths show age differences, especially higher levels throughout adulthood. Ten age groups from early adolescence (10-12 years) to late adulthood (65+ years) were compared for each strength using random-effects models. Overall, significant age differences were found for 23 of the 24 character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 110 publications
(119 reference statements)
3
14
0
2
Order By: Relevance
“…This is in line with earlier research on big fiverelated change goals, which also reported a stronger desire for change in younger samples (Hudson & Fraley, 2016b;Quintus et al, 2017). Given that older people also tend to report higher trait levels of most character strengths (Heintz et al, 2022), one possible explanation is that over the life course, people are somewhat successful in changing their character in the desired direction and therefore, trait levels increase, and the motivation for further change decreases. Cornwell and colleagues (2022) also reported a negative relationship between age and growth motives but also showed that those people who did not follow this trend (i.e., those who maintained their growth motives) reported lower levels of well-being.…”
Section: Change Goals and Agesupporting
confidence: 89%
See 1 more Smart Citation
“…This is in line with earlier research on big fiverelated change goals, which also reported a stronger desire for change in younger samples (Hudson & Fraley, 2016b;Quintus et al, 2017). Given that older people also tend to report higher trait levels of most character strengths (Heintz et al, 2022), one possible explanation is that over the life course, people are somewhat successful in changing their character in the desired direction and therefore, trait levels increase, and the motivation for further change decreases. Cornwell and colleagues (2022) also reported a negative relationship between age and growth motives but also showed that those people who did not follow this trend (i.e., those who maintained their growth motives) reported lower levels of well-being.…”
Section: Change Goals and Agesupporting
confidence: 89%
“…For the character strengths of the VIA classification, a meta-analysis on crosssectional age differences found that most character strengths increase slightly with age (Heintz et al, 2022). In addition, differential relationships between character strengths and well-being have been found across different ages (Baumann et al, 2020;Martínez-Martí & CHARACTER STRENGTHS CHANGE GOALS 6 Ruch, 2014).…”
Section: Are Goals To Change Personality Related To Age?mentioning
confidence: 99%
“…In addition, we report Pearson's correlations based on the sum scale scores. As previous research provided evidence for impact of gender and age on character strengths (e.g., Heintz et al., 2019 ; Heintz & Ruch, 2021 ) and intelligence (e.g., Hartshorne & Germine, 2015 ; Lynn & Irwing, 2004 ), age and gender were controlled for in all analyses regarding the association between fluid intelligence and character strengths. The covariance matrices and the R code for the main analyses are available as Supplemental Online Material, for an inspection of the detailed results (e.g., measurement models).…”
Section: Methodsmentioning
confidence: 99%
“…Generally, CSs were proposed to be slowly increasing by age, but with a dip during adolescence. A recent meta-analysis on cross-sectional studies revealed a significant age difference in 23 of the 24 CSs across the lifespan (from 10 to 65+ years), with 91% of the effects indicating higher levels of the CSs with age, but two CSs (creativity and zest) showed a dip from young (10–12 years) to middle (13–15 years) adolescence (Heintz and Ruch, 2021 ). During adulthood, several cross-sectional studies showed that the trajectory of CSs was generally slowly increasing by age, especially after the age of 18 (Linley et al, 2007 ; Baumann et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%